An Identity of One’s Own. Olympia Morata, a learned lady in the Renaissance - Cagnolati, Antonella (iQual. Revista de Género e Igualdad, 2018)
Abstract Olympia Morata (Ferrara 1526-Heidelberg 1555) is a figure that deserves further insights and research. Woman of deep culture, a writer in Latin and in Greek, she lived at the Este Court of Ferrara at the time when the Duchess Renata of France was spreading the Calvinist religious faith in her entourage. Olympia embraced this faith unreservedly and it costs her escape and exile from Ferrara to take refuge in Germany, where she died at just 29 years. Olympia is therefore a wonderful example of a cultured woman of serious religious devotion, traits that appear in prayer, dialogue, letters, in both Latin and Greek. After her death, from 1558 Celio Secondo Curione collected her literary heritage and published it in various editions. Quite famous in the narrow circle of the Reformed, she was then forgotten and her work still need a good translation from Latin and an appropriate critical edition that overcomes and integrates the one carried out by Lanfranco Caretti in 1940 and 1954. Resumen Olympia Morata (Ferrara 1526-Heidelberg 1555) es una figura que merece que se la investigue con detalle. Mujer de profunda cultura, escritora en latín y en griego, vive en la Corte de los Este de Ferrara en el momento en que la duquesa Renata de Francia difundía la fe religiosa calvinista en su séquito. Olympia abraza esta fe sin reservas y, como consecuencia, tiene que escapar de Ferrara para refugiarse en Alemania, donde muere a los 29 años. Olympia es, por lo tanto, un maravilloso ejemplo de una mujer culta de devoción religiosa seria, aspectos que aparecen en sus oraciones, diálogos y cartas, tanto en latín como en griego. Tras su muerte y desde 1558 Celio Secondo Curione recoge su herencia literaria y la publica en varias ediciones. Muy famosa en el estrecho círculo de la Reformada, Olympia se ha mantenido en el olvido durante mucho tiempo y su producción está pendiente de una buena traducción del latín y una edición crítica apropiada que supere e integre la que llevó a cabo Lanfranco Caretti entre 1940 y 1954. Palabras clave Olympia Morata, mujeres cultas, Renacimiento, Reforma, la corte de los Este, Ferrara.